Protests, Media Coverage, and a Hierarchy of Social Struggle. (October 2019) - Kilgo, Danielle K.; Harlow, Summer
News coverage is fundamental to a protest's viability, but research suggests media negatively portray protests and protesters that challenge the status quo (a pattern known as the protest paradigm). This study questions the validity of those claims within the context of digital newspaper coverage, interrogating how topic and region shape coverage. Using a content analysis of coverage from sixteen newspapers in various U.S. market types and regions, this research examines framing and sourcing features in articles about protests. Results suggest media coverage of protests centered on racial issues (discrimination of Indigenous people and anti-Black racism) follows more of a delegitimizing pattern than stories about protests related to immigrants' rights, health, and environment. A model to understand news coverage of protest based on a hierarchy of social struggle is proposed.